A Needs Analysis of Evaluation Methods in Traditional Dance Learning for Junior High School Students Using Unjumble Activities - Faizah, Alfa; Lestari, Wahyu (Research and Innovation in Social Science Education Journal (RISSEJ), 2025)
This study aims to develop an innovative learning evaluation model through the use of an educational game called Unjumble in an online learning context. Preliminary observations and interviews indicated that the evaluation methods previously used were predominantly conventional and lacked student engagement. To address this issue, Unjumble was designed and implemented within a Project Based Learning (PjBL) framework, where students completed evaluation tasks as part of a structured learning project. The study involved 34 junior high school students at SMP N 1 Pengadegan and employed a descriptive quantitative approach. The effectiveness of Unjumble was examined in terms of efficiency and practicality, which were measured through task completion time, student performance scores, and questionnaire responses from students and teachers. The findings indicate that Unjumble can support more interactive and manageable online evaluation activities, although the results are limited by the small sample size and the absence of a control group. This study suggests that game based evaluation tools integrated with PjBL have potential to support the goals of the independent curriculum, particularly in promoting creative and engaging assessment practices, while acknowledging the need for further large scale and comparative studies.